KONSEP DIRI REMAJA MANTAN PECANDU NARKOBA DITINJAU DARI DUKUNGAN SOSIAL: KONSEP DIRI REMAJA MANTAN PECANDU NARKOBA DITINJAU DARI DUKUNGAN SOSIAL - Sry Hasriny; Muh Aswar Mustari (JURNAL PSIKOLOGI SKIsO (Sosial Klinis Industri Organisasi), 2020)
Abstract: Stress in early adulthood is viewed from online gambling addiction. This study aims to determine the relationship between online gambling addiction and stress in early adulthood. This research uses quantitative methods. The population in this study were internet cafe visitors in the city of Makassar who played online gambling games and were in early adulthood. The population in this study were 51 online gambling players. The subjects in this study were 33 people using simple random sampling. The results of this study were analyzed using the Pearson product moment correlation showing a number of 0.078 with P = 0.002 (P <0.05), this indicates that the influence between the two is significant, so the research hypothesis is accepted. This means that the higher the online gambling addiction, the higher the stress in early adulthood.